Improvement of drug release and its efficacy in cancer treatment with advanced encapsulation methods in a novel hydrophobic agent into human serum albumin nanoparticles - Mehrnaz Yadini; Maryam Saeidifar; Nader Nezafati; Seyed Mojtaba Daghighi (Results in Chemistry)
The pharmacological properties of curcumin and its derivatives, such as anti-inflammatory, antibacterial, and anticancer effects, demonstrated superior qualities and encapsulation of curcumin derivatives in biocompatible nanocarriers holds great potential for enhancing the efficacy, improving solubility and safety of this promising agents. This study focuses on encapsulating the curcumin derivative 2,6-bis(3,4-diMethoxyBenzylidene)-1-Cyclohexanone (MBC) in human serum albumin nanoparticles (HSANP) through two methods: incubation (MBC@HSANP) and in-situ encapsulation (MBC.HSANP). The aim is to compare drug release and anticancer activity. Characterization of the colloidal drug carriers involved various analysis techniques such as FTIR, UV–vis, XRD, DSC, DLS, FESEM, and contact angle analysis, confirming the successful encapsulation of MBC in HSANP. The drug loading percentage (%DL) was found to be 8.85 % ± 0.06 and 7.73 % ± 0.37 for MBC@HSANP and MBC.HSANP, respectively, with encapsulation efficacy percentage (%EE) of 97.09 % ± 0.78 and 83.75 % ± 4.39. The nanocarriers exhibited spherical shapes with average particle sizes of 92 nm as well as lower agglomeration, and more hydrophilicity in MBC.HSANP (WCA of 110°) compared to MBC@HSANP (WCA of 86°). The release of MBC from the two systems was sustained compared to free MBC and MBC loaded onto HSA, following the Korsmeyer−Peppas kinetic model and non-Fickian transport behavior. Furthermore, the release of MBC from the MBC.HSANP system was lower than that of the MBC@HSANP system due to the entrapment of MBC into HSANP. Cellular evaluation on breast cancer cell lines (MCF7) showed higher safety in MBC.HSANP compared to MBC and MBC@HSANP, likely due to the more sustained release of MBC from MBC.HSANP system and induction of apoptosis was mentioned in MBC.HSANP and MBC@HSANP. These findings suggest the potential for sustained drug release and improved therapeutic efficacy in treating breast cancer cells.